Escolas fundamentalista e técnica: performance de previsão de retorno no mercado de fundos de investimento em ações do Brasil - Lopes, Stefano Almeida (2010)
In this paper it was analized the prediction performance of shares investments funds in Brazil by the fundamentalist and technical methodology. For the fundamentalist analysis it was use the CAPM (Capital Asset Pricing Model) and for the technical analysis the moving average. The data base used embraced 75 funds with a series of 120 observations for each one. The results pointed out that the CAPM showed a better performance in the forecast. The technical analysis is not the most indicated model to try to forecast the returns on investments share funds. Even though, it has been observed that this methodology provides sign of the moment to buy and sell the funds quotas.